The Influence of Brand Image and Service Quality on Customer Satisfaction of Export-Import Shipping Services at Evergreen Line - Masdiah Lolita Rithanis Samosir; Damajanti Sri Lestari; Listyawati, Liling (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the influence of brand image and service quality on customer satisfaction of export-import shipping services on Evergreen Line. This study uses a quantitative approach with a survey method. The research sample amounted to 96 respondents who were users of Evergreen Line services in the export-import documentation division. The data collection technique was carried out through a questionnaire with a Likert scale, while the data analysis technique used multiple linear regression accompanied by a classical assumption test, F test, t test, and determination coefficient. The results of the study show that simultaneously brand image and service quality have a significant effect on customer satisfaction. Partially, service quality has a positive and significant effect on customer satisfaction, while brand image does not have a significant effect on customer satisfaction. The determination coefficient value of 0.742 showed that 74.2% of the variation in customer satisfaction could be explained by brand image and quality of service, while the rest was influenced by other variables outside the research model. This finding indicates that improving service quality is the main factor in building customer satisfaction of export-import shipping services on Evergreen Line.